AI-Based Learning Design Strategy for Teachers of State Junior High School 1 Surakarta in Improving Student Integrity and Cognition - Putri, Febriyani Amelia; Dartim, Dartim (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the strategies of SMP Negeri 1 Surakarta teachers in designing AI-based learning to improve students' academic integrity and cognitive abilities. The research uses qualitative methods with case study design and phenomenological approaches. Data was collected through in-depth interviews and literature studies to understand teachers' practices and perceptions in depth. The use of AI is instrumental and selective, especially for efficiency in the preparation of teaching materials and learning administration. The Learning Community Collaboration Forum (KomBel) is an important forum to share practices and filter ideas for the use of technology. The school applies a controlled mediation model to technological supervision, while academic integrity is built through strict rules and internalization of values. Cognitive differentiation strategies were developed by teachers even though the use of AI for adaptive personalization was not optimal. The study shows that the success of AI integrity depends on the central role of teachers as designers, facilitators, and integrity guards, as well as the synergy between technology and traditional pedagogical wisdom. The implementation of AI is effective when positioned as a complement (tool) within a strong policy framework and school culture.